Analisis Tingkat Penerimaan Mahasiswa Terhadap Cloud File Hosting Services dengan Metode Technology Acceptance Model - Andrianus Bennyanto; Marcelli Indriana (Universitas Multimedia Nusantara, 2015)
There are many mobile and desktop apps available to use for free. Starting from games to productivity apps. One type of productivity apps is cloud file hosting services such as Dropbox and Google Drive. This study aims to determine how Dropbox and Google Drive are accepted to the users. Not just want to get the factors of acceptance, but to get the root of the acceptance. By using the methodology of technology acceptance model and relying on statistical calculations of structural equation modeling software LISREL, the level of acceptance of these two popular applications will be known. Index Terms - Cloud Fire Hosting Services, Level of Acceptance, Technology Acceptance Model, Structural Equation Modelling, LISREL.